Innate and evolutionarily increased advantages of invasive Eupatorium adenophorum over native E. japonicum under ambient and doubled atmospheric CO2 concentrations - Yan Bao Lei; Yu Long Feng; Yu Long Zheng; Rui Fang Wang; He De Gong; Yi Ping Zhang (Biological Invasions, 2011)

Variation in the internalization of differently sized nanoparticles induces different DNA-damaging effects on a macrophage cell line - Mingyi Zhang; Juan Li; Gengmei Xing; Rui He; Wei Li; Yan Song; Haili Guo (Archives of Toxicology, 2011)

Yield estimation of winter wheat in the North China Plain using the remote-sensing–photosynthesis–yield estimation for crops (RS–P–YEC) model - Peijuan Wang; Rui Sun; Jiahua Zhang; Yuyu Zhou; Donghui Xie; Qijiang Zhu (International Journal of Remote Sensing, 2011)

Influence of sCD40L on gastric cancer cell lines - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Xue-Guang Zhang (Molecular Biology Reports, 2011)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

Two Types of Phytases (Histidine Acid Phytase and β-Propeller Phytase) in Serratia sp. TN49 from the Gut of Batocera horsfieldi (Coleoptera) Larvae - Rui Zhang; Peilong Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Bin Yao (Current Microbiology, 2011)

Homology modeling, molecular docking and spectra assay studies of sterol 14α-demethylase from Penicillium digitatum - Shuxiang Li; Jianhua Zhang; Shufen Cao; Rui Han; Yongze Yuan; Jiangke Yang; Yunjun Yan; Deli Liu (Biotechnology Letters, 2011)

Microsatellite DNA markers for mating systems analysis in the Leishan moustache toad (Vibrissaphora leishanensis) - Juan Wang; Jian Cheng; Rui-Ping Zhang; Yong-Zhen Wang; Chen-Liang Li; Hua Wu (Conservation Genetics Resources, 2011)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Retinoids induced Pck1 expression and attenuated insulin-mediated suppression of its expression via activation of retinoic acid receptor in primary rat hepatocytes - Yan Zhang; Rui Li; Wei Chen; Yang Li; Guoxun Chen (Molecular and Cellular Biochemistry, 2011)

Changes in bacterial community of anthracene bioremediation in municipal solid waste composting soil - Shu-ying Zhang; Qing-feng Wang; Rui Wan; Shu-guang Xie (Journal of Zhejiang University-SCIENCE B, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Assessing land ecological security in Shanghai (China) based on catastrophe theory - Shiliang Su; Dan Li; Xiang Yu; Zhonghao Zhang; Qi Zhang; Rui Xiao; Junjun Zhi; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2011)

Assessment of spatial distribution of soil loss over the upper basin of Miyun reservoir in China based on RS and GIS techniques - Tao Chen; Rui-qing Niu; Yi Wang; Ping-xiang Li; Liang-pei Zhang; Bo Du (Environmental Monitoring and Assessment, 2011)

Aerosol size distributions in urban Jinan: Seasonal characteristics and variations between weekdays and weekends in a heavily polluted atmosphere - Pengju Xu; Wenxing Wang; Lingxiao Yang; Qingzhu Zhang; Rui Gao; Xinfeng Wang; Wei Nie; Xiaomei Gao (Environmental Monitoring and Assessment, 2011)

Plasminogen K5 activates mitochondrial apoptosis pathway in endothelial cells by regulating Bak and Bcl-xL subcellular distribution - Xiaoqiong Gu; Yachao Yao; Rui Cheng; Yang Zhang; Zhiyu Dai; Genping Wan; Zhonghan Yang; Weibin Cai; Guoquan Gao; Xia Yang (Apoptosis, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Production of Chitinase and its Optimization from a Novel Isolate Serratia marcescens XJ-01 - Jin-Lan Xia; Jing Xiong; Rui-Yong Zhang; Ke-Ke Liu; Bin Huang; Zhen-Yuan Nie (Indian Journal of Microbiology, 2011)

Integration of gene chip and topological network techniques to screen a candidate biomarker gene (CBG) for predication of the source water carcinogenesis risks on mouse Mus musculus - Jie Sun; Shupei Cheng; Aimin Li; Rui Zhang; Bing Wu; Yan Zhang; Xuxiang Zhang (Ecotoxicology, 2011)

Time-dependent oxidative stress and histopathological changes in Cyprinus carpio L. exposed to microcystin-LR - Jinlin Jiang; Xueyuan Gu; Rui Song; Qian Zhang; Jinju Geng; Xiaorong Wang; Liuyan Yang (Ecotoxicology, 2011)

Preliminary evaluation of gene expression profiles in liver of mice exposed to Taihu Lake drinking water for 90 days - Yan Zhang; Weixin Li; Rui Zhang; Jie Sun; Bing Wu; Xuxiang Zhang; Shupei Cheng (Ecotoxicology, 2011)

Risk assessment of polycyclic aromatic hydrocarbons in aquatic ecosystems - Bing Wu; Rui Zhang; Shu-Pei Cheng; Timothy Ford; Ai-Min Li; Xu-Xiang Zhang (Ecotoxicology, 2011)

Genome-wide screening of indicator genes for assessing the potential carcinogenic risk of Nanjing city drinking water - Rui Zhang; Shupei Cheng; Aimin Li; Jie Sun; Yan Zhang; Xuxiang Zhang (Ecotoxicology, 2011)

NMR-based metabolic profiling for serum of mouse exposed to source water - Yan Zhang; Weixin Li; Jie Sun; Rui Zhang; Bing Wu; Xuxiang Zhang; Shupei Cheng (Ecotoxicology, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Pollen morphology of Hosta Tratt. in China and its taxonomic significance - Jia-Xi Liu; Chun-Hai Zhao; Xiao-Rui Liu; Yi-Zhen Xi; Yu-Long Zhang (Plant Systematics and Evolution, 2011)

Localized Delivery of Antisense Oligonucleotides by Cationic Hydrogel Suppresses TNF-α Expression and Endotoxin-Induced Osteolysis - Lei Dong; Zhen Huang; Xing Cai; Jiawei Xiang; Yi-An Zhu; Rui Wang; Jiangning Chen; Junfeng Zhang (Pharmaceutical Research, 2011)

Molecular cloning and characterization of GhAPm, a gene encoding the μ subunit of the clathrin-associated adaptor protein complex that is associated with cotton (Gossypium hirsutum) fiber development - Tao Zhou; Rui Zhang; Dawei Yang; Sandui Guo (Molecular Biology Reports, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

Cloning and characterisation of a novel 2,4-dichlorophenol hydroxylase from a metagenomic library derived from polychlorinated biphenyl-contaminated soil - Yang Lu; Ying Yu; Rui Zhou; Wei Sun; Chunyan Dai; Pei Wan; Lanying Zhang; Dongyun Hao; Hejun Ren (Biotechnology Letters, 2011)

A strategy to deal with water crisis under climate change for mainstream in the middle reaches of Yellow River - Xiao-jun Wang; Jian-yun Zhang; Rui-min He; ElMahdi Amgad; ElSawah Sondoss; Man-ting Shang (Mitigation and Adaptation Strategies for Global Change, 2011)

An improved classification method for hyperspectral data based on spectral and morphological information - Zuchuan Li; Liwei Li; Rui Zhang; Jianwen Ma (International Journal of Remote Sensing, 2011)

Effects of Copper Exposure on Expression of Glutathione-Related Genes in Acidithiobacillus ferrooxidans - Jin-lan Xia; Shun Wu; Rui-yong Zhang; Cheng-gui Zhang; Huan He; Hong-chen Jiang; Zhen-yuan Nie; Guan-zhou Qiu (Current Microbiology, 2011)

Dynamics of vegetation and soil carbon and nitrogen accumulation over 26 years under controlled grazing in a desert shrubland - Zhi-Yu Zhou; Feng-Rui Li; Shan-Ke Chen; Hong-Rong Zhang; Guangdi Li (Plant and Soil, 2011)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Synthesis, Crystal Structure, Interaction with BSA and Antibacterial Activity of La(III) and Sm(III) Complexes with Enrofloxacin - Yan-Jun Wang; Rui-Ding Hu; Dong-Hua Jiang; Ping-Hua Zhang; Qiu-Yue Lin; Yun-Yun Wang (Journal of Fluorescence, 2011)

Paracoccus beibuensis sp. nov., Isolated from the South China Sea - Qiang Zheng; Yanan Wang; Chuang Chen; Yu Wang; Xiaomin Xia; Yingnan Fu; Rui Zhang; Nianzhi Jiao (Current Microbiology, 2011)

Fatty acid composition of Camellia oleifera oil - Jinlin Ma; Hang Ye; Yukui Rui; Guochen Chen; Naiyan Zhang (Journal of Consumer Protection and Food Safety, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

A three-dimensional finite element model of the cervical spine: an investigation of whiplash injury - Jian-Guo Zhang; Fang Wang; Rui Zhou; Qiang Xue (Medical & Biological Engineering & Computing, 2011)

Identification of novel serum biomarkers in child nephroblastoma using proteomics technology - Qian Zhang; Jiaxiang Wang; Rui Dong; Shaobo Yang; Shu Zheng (Molecular Biology Reports, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Influence of soluble microbial products (SMP) on wastewater disinfection byproducts: trihalomethanes and haloacetic acid species from the chlorination of SMP - Yuan-yuan Wei; Yan Liu; Yun Zhang; Rui-hua Dai; Xiang Liu; Jin-jian Wu; Qiang Zhang (Environmental Science and Pollution Research, 2011)